2018
DOI: 10.4172/2576-1420.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Improving STI and HIV Passive Partner Notification Using the Model for Improvement: A Quality Improvement Study in Lilongwe Malawi

Abstract: Background:In Malawi, passive partner notification is the mainstay method of partner notification (PN). Despite its wide use, the proportion of sexual partners referred for care through this method is very low. We aimed to increase the proportion of sexual partner referral through passive PN.Methods:We implemented a quality improvement (QI) project at Bwaila STI unit in Lilongwe, Malawi between January and June 2017 using a pre- and post- intervention quasi-experimental study design. Pre-intervention, we condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This is in line with prior research in Southern Africa, suggesting enhanced counseling, contact slips, extended clinic hours, and expedited clinic flow for sex partners increased partner notification and treatment. 16,17 Additionally, a systematic review found that supplemented notification strategies, such as providing educational information for partners, were as effective in preventing reinfection as EPT. 9 Our study provides further evidence that such low-cost interventions may increase partner treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with prior research in Southern Africa, suggesting enhanced counseling, contact slips, extended clinic hours, and expedited clinic flow for sex partners increased partner notification and treatment. 16,17 Additionally, a systematic review found that supplemented notification strategies, such as providing educational information for partners, were as effective in preventing reinfection as EPT. 9 Our study provides further evidence that such low-cost interventions may increase partner treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MSc students publish as well, and in 2017 and 2018, both the FIC and WHO grants supported students to attend international research conferences. The students from the 2016 and 2017 cohorts had 12 publications in peer-reviewed journals (Eboreime, Eyles, Nxumalo, Eboreime, & Ramaswamy, 2019; Eboreime, Nxumalo, et al, 2019; Manyeh, Ibisomi, Baiden, Chirwa, & Ramaswamy, 2019; Manyeh, Nathan, & Nelson, 2018; Matoga, Hosseinipour, et al, 2018; Matoga, Mmodzi, et al, 2018; McGavin et al, 2018; Naidoo, Railton, Jobson, et al, 2018; Naidoo, Railton, Khosa, et al, 2018; Naidoo, Zuma, et al, 2018; Naidoo, Matlakala, et al, 2019; Wambiya, Atela, Eboreime, & Ibisomi, 2018) and eight poster presentations.…”
Section: Accomplishments To Datementioning
confidence: 99%